The Need for Specialist Doctors in the Development of Type B General Hospital at Regional Level - Desy Martha Panjaitan; Widyana Beta Arthanti; Mokhamad Khoirul Huda (Indian Journal of Forensic Medicine & Toxicology, 2021)
Regulation of the Minister of Health No. 3 of 2020 on Hospital Classification stated the classification of a hospital is no longer based on the number of specialist and subspecialty services as in the previous provisions, but rather emphasizes the number of beds. However, type B hospitals’ problem is not the number of beds, but the lack of complete facilities, the availability of human resources such as the need for specialist doctors and the unequal distribution of type B hospitals at the regional level. This research aims to find out programs to fulfil the needs for specialist doctors in developing type B hospitals at the regional level. The results showed that the program to fulfil the needs for specialist doctors of type B hospital in the region could be as shortterm, medium-term and long-term programs. Specialist doctor education scholarship programs are a better solution to fulfil type B hospitals’ needs at the regional level. Thus, the fulfilment of the need for specialist doctors will improve the quality of health services.